Design and techno‐economic analysis of plug‐in electric vehicle‐integrated solar PV charging system for India. Issue 2 (27th February 2019) - Shrivastava, Prashant; Alam, Mohammad Saad; Asghar, Mohammad Syed Jamil
Abstract : Electrified transportation technology has matured in different parts of the globe. However, this technology is in an advent stage in the Indian market. Due to this fact, a lot more challenges are being encountered in the development of electrified transportation in India; with the scarcity of viable charging stations posing as a significant bottleneck. In this study, the techno‐economic analysis of different solar‐based charging schemes that are available in the existing environment and present a modest, economical and reliable method of charging an electric vehicle (EV))(e.g. e‐rickshaw) through a solar panel that ultimately enhances the driving range and overall reliability of the system has been done. To validate the performance, the prototype of vehicle‐integrated photovoltaic (PV) charging system has been developed and test results are demonstrated. Economic analysis is done based on the yearly average solar irradiance profile in Aligarh, India. Further, this work presents a comparative analysis of CO2 emission for 100 km driving range from the EVs charge by different charging schemes and internal combustion engine vehicles.